'[A] poet must know more than | a surface suggests': Reading and Secrecy in the Poetry of Anna Mendelssohn. Issue 1 (26th March 2018) - Sparrow, Vicky
Abstract : In stating that a 'poet must know | more than a surface suggests' ( Propaganda multi-billion bun ), Anna Mendelssohn ascribes to the poet a kind of secret knowledge of that which resides beyond the apparent meaning of a poem, beneath its textual surface or skin. This article considers how far a reader of Mendelssohn's poetry can be invited to share in this knowledge – on what grounds and at what risk. Mendelssohn's construction of such hidden poetic knowledge is also considered in the light of Walter Benjamin's contention that the secret is of fundamental importance to the production of aesthetic experience itself. If a reader of Mendelssohn 'mustn't touch the hiding places' ( Implacable Art ) of a text, then how do we, as readers, offer close, interpretive attention to Mendelssohn's difficult, implacable poetry without intruding on its secrets? In foregrounding close-readings of one of Mendelssohn's most encoded texts, her pamphlet An Account of a Mummy, in the Royal Cabinet of Antiquities at Dresden (1986), textual disruptions of the relationship between concealment and exposure, and questions of readability and unreadability are explored. Teasing out moments of poetic secreting and revealing in Mendelssohn's work, this article considers how far Mendelssohn's poetics resists the logic of interrogation – and asks, crucially, what is at stake in such resistance for a close-reader of her poetry.